The oonopid spider genus Ischnothyreus in Borneo (Oonopidae, Araneae) - Kranz-Baltensperger, Yvonne (Zootaxa, 2011)
The genus Ischnothyreus is reported for the first time from Borneo with 17 new species (I. balu, I. barus, I. danum, I. deelemanae, I. elvis, I. falcifer, I. flabellifer, I. flippi, I. florifer, I. fobor, I. hooki, I. jojo, I. kalimantan, I. matang, I. mulumi, I. rex, I. serapi). All species are diagnosed, described and illustrated.